Features of misogynistic discourse as based on red pill discourse analysis - Polkowska, Laura (Papers in Linguistics, 2026)
This text examines linguistic features of misogynistic discourse, focusing on statements made by representatives of the so-called red pill movement – a men’s rights movement operating within the Polish manosphere. The analysis reveals that this discourse is formally inconsistent, blending elements of quasi-scientific and community discourse, but primarily the discourse of exclusion. Its defining characteristics include: schematic narration, manifested in a simplified presentation of female–male relations and the reduction of representatives of both sexes to reproductive functions; categorical language, described by Michał Głowiński as the rhetoric of absolute certainties; binary reasoning that comes down to a black-and-white vision of reality; projectivity, which consists in using incidental examples to construct universal visions; and seemingly revealing nature of this discourse, stemming from the conviction that the surrounding world is founded on a falsehood. Women are discredited through nominations defining them, dehumanizing metaphors, and comparisons. Key argumentative patterns employed by red pill proponents include: an argument referring to evolution (a biological one), an argument referring to survival (a pragmatic one), an argument referring to privilege (a social one), and an argument referring to subconscious needs (a psychological one). Misogynistic discourse of the red pill exemplifies a discourse of exclusion, grounded in hate speech.